(untitled) (Conference on English Language Teaching, 2023)
This study describes linguistic phenomena of conversation from the students fight at school, this research is linguistic forensics. This purpose is to identify student utterances which caused fighting and to identify the legal implications that arise as a result of student fight using forensic linguistic study. This study uses a descriptive qualitative approach. Data collection techniques are the recording and interviewing by Counselling teacher. The results of this study indicate that students who fight at school frequently cover up their mistakes by providing convoluted information when the teacher or counselling teacher investigated the causes of students fighting. The counselling teacher’s questions sometime seem to corner, accuse, threaten, and offend make students feel uncomfortable and result in students being dishonest. This can be seen from the answers given by the students to Counselling teacher. During the interrogation process, the counselling teacher should analyse the conversation between teacher and students to analyse the conversation. Then, how to analyse the conversation, the counselling teacher will use Grice’s cooperative principle. In addition, the Counselling teacher need to pay attention to the language patterns used when interrogating the students so that the students can provide information about committed without pressure and violence.